The Role of Motor Learning in Improving Physical and Mental Balance of Physical Education Students - Indra Adi Budiman; Davi Sofyan; Nugroho Susanto (Universitas Majalengka, 2024)
The development of mental and physical equilibrium depends heavily on motor learning, especially for physical education students who need both abilities to succeed in their work. This study aims to investigate how well motor learning may improve university-level physical education students' mental stability and physical coordination. The study uses a mixed-methods approach, integrating qualitative observations and interviews with quantitative investigations. 60 physical education students participated, split into two groups: the experimental group and the control group. For 12 weeks, the control group followed their usual physical education curriculum, while the experimental group participated in a motor learning program that included activities aimed at improving their gross motor skills, fine motor skills, and cognitive-motor integration. Physical balancing tests, mental health evaluations, and reflective journals were used to gather data. The results showed that, compared to the control group, the experimental group's physical balance significantly improved (p < 0.05). Qualitative data also showed that participants in the experimental group had improved emotional regulation, decreased anxiety, and increased mental focus. These results demonstrate the potential advantages of systematic motor learning programs for mental and physical health. To sum up, motor learning is an essential part of physical education that supports students' overall development. To maximize student performance and prepare them for the sector's complex needs, universities should incorporate focused motor learning activities into their physical education curricula. The long-term impacts of such interventions on various populations should be investigated in more detail.